Pengaruh Kualitas Layanan dan Kualitas Produk terhadap Loyalitas Pelanggan di Era Pandemi Covid-19: Studi pada PT Pos Indonesia Cabang Yogyakarta - Rinda Aprilia Pramesti; Niken Widyastuti; Heri Winarto (Universitas Proklamasi 45, 2024)
This study aims to determine: (1) The effect of service quality on customer loyalty PT. Pos Indonesia Yogyakarta branch. (2) The effect of product quality on customer loyalty of PT. Pos Indonesia Yogyakarta branch. (3) The effect of service quality and product quality partially on customer loyalty PT. Pos Indonesia Yogyakarta branch. This research is quantitative research. The population in this study are customers who use the services of PT. Pos Indonesia Yogyakarta branch with a total of 108,000 customers taken in the last 3 years and a sample of 100 customers was taken as research respondents with the determination of the number using the Slovin formula. The sampling technique used is accidental. Data collection techniques using a questionnaire or questionnaire. And the data analysis techniques in this study used data descriptions, validity, and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study indicate the quality of service and product quality in the era of the covid-19 pandemic at PT. Pos Indonesia Yogyakarta branch partially or jointly proved to have a positive and significant effect on customer loyalty at P. Pos Indonesia Yogyakarta branch.